Chicago Lawyers Survey, 1994-1995 - Heinz, John P. ([Verlag nicht ermittelbar], 2006)
Conducted as a partial replication of the CHICAGO LAWYERS SURVEY, 1975 (ICPSR 8218), this 1994-1995 survey sought to analyze the processes of change that transformed the practice of law and the market for legal services over the two decades between 1975 and 1995. Randomly selected Chicago, Illinois, lawyers were asked about, for example, the nature of their work, work settings, fields of practice, job satisfaction, career histories, professional commitment, client characteristics, and social and political values. Results revealed important changes in the legal profession between 1975 and 1995: women entered the profession in substantial numbers, new specialties were created, law firms and corporate legal departments grew dramatically, and in many organizations the practice of law became constrained by bureaucratic rules and procedures. Background information includes state of residence during high school, college or university attended, law school attended, law school class rank, political preference, degree of political party affiliation, religious preference, marital status, nationality, year of birth, income, race, zip code, number of children, work status of spouse, spouse's nationality, respondents' mother's occupation, respondents' mother's law school, respondents' father's occupation, and respondents' father's law school.